Toronto : The Monocle Travel Guide (Berlin : Gestalten, 2016)
Toronto may boast one of the world's most famous skylines but beneath the iconic pinprick of the CN Tower lies a burgeoning city that has become one of North America's most intriguing and surprising urban centres. It has long offered a warm reception to those coming from afar and today this is evident in the diverse cultural landscape comprising everything from tango dance halls and Portuguese restaurants to Italian radio stations and Ukrainian churches. The Monocle Travel Guide to Toronto will help you experience the city's celebrated hospitality to its fullest. We'll show you the dining spots offering ambitious menus that draw on the city's multicultural make-up and the cosiest bars and coffee shops. Then there are the innovative ateliers, architects and fashion houses shaping Toronto's visual vocabulary, the top venues in which to delve into the thriving arts and music scene and the most picturesque routes for an early.
Keywords: Reisgids; Toronto